Heat stress transcripts, differential expression, and profiling of heat stress tolerant gene TaHsp90 in Indian wheat (Triticum aestivum L.) cv C306 - Vishwakarma, Harinder; Junaid, Alim; Manjhi, Jayanand; Singh, Gyanendra Pratap; Gaikwad, Kishor; Padaria, Jasdeep Chatrath (PloS one, 2018)
To generate a genetic resource of heat stress responsive genes/ESTs, suppression subtractive hybridization (SSH) library was constructed in a heat and drought stress tolerant Indian bread wheat cultivar C306. Ninety three days old plants during grain filling stage were subjected to heat stress at an elevated temperature of 37°C and 42°C for different time intervals (30 min, 1h, 2h, 4h, and 6h). Two subtractive cDNA libraries were prepared with RNA isolated from leaf samples at 37°C and 42°C heat stress. The ESTs obtained were reconfirmed by reverse northern dot blot hybridization. A total of 175 contigs and 403 singlets were obtained from 1728 ESTs by gene ontology analysis. Differential expression under heat stress was validated for a few selected genes (10) by qRT-PCR. A transcript showing homology to Hsp90 was observed to be upregulated (7.6 fold) under heat stress in cv. C306. CDS of TaHsp90 (Accession no. MF383197) was isolated from cv. C306 and characterized. Heterologous expression of TaHsp90 was validated in E. coli BL21 and confirmed by protein gel blot and MALDI-TOF analysis. Computational based analysis was carried out to understand the molecular functioning of TaHsp90. The heat stress responsive SSH library developed led to identification of a number of heat responsive genes/ESTs, which can be utilized for unravelling the heat tolerance mechanism in wheat. Gene TaHsp90 isolated and characterized in the present study can be utilized for developing heat tolerant transgenic crops.